Etika Politik Terhadap Perilaku Korupsi di Indonesia (Studi Kasus DPRD Kota Malang) - Alim, Ashari Sakti; Salmawati, Salmawati; Rahmawati, Dian Eka (Universitas Muhammadiyah Sorong, 2021)
This paper wants to discuss how political ethics can influence corruption behavior in Indonesia and more specifically in the legislative.Â To answer the formulation of the problem in this paper, the writer uses the researce library research method, which is conducting in-depth studies through journals, books and documents. Speaking of corruption is not just how we understand about state losses. But this is a matter of ethics, moral issues, behavior problems and national problemsÂ the death of political ethics makes deviant behavior of the stakeholders and also freezes political ethics among elites making a lot of great shocks that can be seen with so much corruption in this country